Use of the PROMIS Depression Scale and the Beck Depression Inventory in Patients with Heart Failure - Freedland, Kenneth E. (Health Psychol, 2019)
OBJECTIVE: This study evaluated agreement between the PROMIS Depression scale and the Beck Depression Inventory (BDI-II) in patients with heart failure and comorbid major depression. METHOD: The BDI-II and the computerized adaptive test version of the PROMIS Depression scale were administered at baseline to 158 participants in a randomized controlled trial of cognitive behavior therapy for major depression in patients with heart failure. A crosswalk table (Choi, Schalet, Cook, & Cella, 2014) was used to transform the PROMIS scores into “linked” BDI-II equivalent scores. Bland-Altman plots, histograms, and scatterplots were used to visualize the agreement between these scores at baseline and 6 months, and intraclass correlation coefficients (ICCs) were calculated for each occasion to quantify the agreement. Treatment effects and change scores were also examined. RESULTS: The measures agreed moderately at baseline (ICC, 0.52; p<.0001) and strongly at 6 months (ICC, 0.77; p<.0001), but on average, the linked and observed BDI-II scores differed by 3.1 points at baseline (p<.0001) and −0.17 points at 6 months (p=.78). The discrepancies were considerably larger in many individual cases on both occasions. CONCLUSIONS: The PROMIS Depression scale is likely to play an important role in research on depression in patients with heart failure, but for now, it should be used in addition to rather than instead of the BDI-II in studies in which the BDI-II would ordinarily be used. Additional research is needed to evaluate the validity and utility of the PROMIS Depression scale in patients with heart failure.